PENGARUH KOMPETENSI APARAT DESA DAN TINGKAT PENDIDIKAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Pada Aparat Desa Se Kecamatan Walea Besar Kabupaten Tojo Una-Una) - Mattoasi, Mattoasi; Sapeni, Aston; Musue, Didiet Pratama (Program Studi Akuntansi, 2020)
This study aims to determine the effect of the competence of village officials and education and training simultaneously on the accountability of village fund financial management by the Village Government in Walea Besar District, Tojo Una-Una Regency partially or simultaneously. This research is a quantitative study. The population in the study was 113 village officials, then the sampling method was purposive sampling so that the sample in the study was 39 people. The results of this study indicate that the competence of village officials and the education and training of village officials partially or simultaneously have a significant effect on the accountability of village fund management in the village of Walea Besar District, Tojo Una-Una Regency. The value of Ajusted R Square is 0.622. This value shows that 62.2% of the variability of village fund management accountability in the Village in Walea Besar District, Tojo Una-Una Regency can be explained by the competence of village officials and education and training of village officials, while the remaining 37.8% can be explained by other variables. which were not examined in this study were the variables of the role of the village head and the awareness of the apparatus.